Negative electrode material, secondary battery, and electric device

By introducing C-S and S-S keys into the negative electrode material of the secondary battery and controlling its performance parameters, the problem of long charging time of the secondary battery is solved, and the specific capacity and rate performance of the battery are significantly improved, which is suitable for fast charging applications of new energy vehicles.

CN120221635APending Publication Date: 2025-06-27SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510529238.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The charging time of existing secondary batteries is long, making it difficult to meet the range needs of new energy vehicles, especially in fast charging applications.

Method used

By designing a negative electrode material containing C-S bonds and S-S bonds, the specific surface area, porosity, the ratio of the D peak intensity and G peak intensity of the Raman spectrum, and the ratio of the sum of the C-S peak and S-S peak areas in the XPS spectrum to the S2p peak area are controlled, so as to meet a specific performance range to improve the adsorption and transfer capacity of sodium ions.

Benefits of technology

It significantly improves the specific capacity and rate performance of the secondary battery, shortens the diffusion path of sodium ions, enhances the conductivity and stability of the material, and improves the fast charging performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005378610690000121
    Figure BDA0005378610690000121
  • Figure BDA0005378610690000131
    Figure BDA0005378610690000131
  • Figure BDA0005378610690000132
    Figure BDA0005378610690000132
Patent Text Reader

Abstract

The invention discloses a negative electrode material, a secondary battery and an electric device, and belongs to the technical field of batteries, the performance and the specific surface area of the negative electrode material, the ratio of the Raman spectrum D peak intensity to the Raman spectrum G peak intensity, the porosity, and the proportion of the sum of the C-S peak area and the S-S peak area to the S2p peak area are controlled to meet the following relation: 0.74 < = Y < = 1.30; the desolvation capability of sodium ion salt in the electrolyte and the rapid adsorption and mass transfer capability of sodium ions are promoted, the adsorption energy of the sodium ions on the hard carbon surface is improved, the transfer of the sodium ions is promoted, the ion conductivity of the negative electrode material can be effectively improved, the diffusion path of the sodium ions is shortened, more active sites are provided, and the embedding and separation of the sodium ions are promoted; the diffusion rate of sodium ions is improved, and the specific capacity and the rate capability of the secondary battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of batteries, and particularly to a negative electrode material, a secondary battery, and an electrical device. Background Art

[0002] A secondary battery refers to a battery that can be reversely charged through an external power source to restore its electrical energy. Different from a primary battery (non-rechargeable battery), a secondary battery can restore its charge through charging after releasing energy during discharge, so it has the characteristic of being reusable. Secondary batteries are widely used in many fields such as portable electronic devices, electric vehicles, and energy storage systems.

[0003] With the continuous popularization of new energy vehicles and the continuous investment of researchers in the energy density of secondary batteries, the energy density of secondary batteries has made remarkable progress, which can better meet people's needs for the cruising range of new energy vehicles. However, the long charging time of new energy vehicles has become a current pain point and has received extensive attention in the industrial community. The research and development of fast-charging sodium-ion batteries is imminent.

[0004] In view of this, this application is proposed.

[0005] Content of the Application

[0006] The purpose of this application is to overcome the deficiencies of the prior art and provide a negative electrode material, a secondary battery, and an electrical device, which have excellent specific capacity and rate performance.

[0007] To achieve the above object, a first aspect of this application provides a negative electrode material, which contains C-S bonds and S-S bonds;

[0008] The negative electrode material satisfies: 0.74 ≤ Y ≤ 1.30;

[0009] Wherein, Am 2 / g is the specific surface area of the negative electrode material;

[0010] Q% is the porosity of the negative electrode material;

[0011] γ is the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum of the negative electrode material;

[0012] B% is the proportion of the sum of the areas of the C-S peak and the S-S peak in the XPS spectrum of the negative electrode material to the area of the S2p peak.

[0013] As an embodiment of this application, it satisfies at least one of the following (Ⅰ) to (Ⅳ):

[0014] (Ⅰ) 300 ≤ A ≤ 1000;

[0015] (II) 38 ≤ Q ≤ 68;

[0016] (III) 1.05 ≤ γ ≤ 1.4;

[0017] (IV) 48 ≤ B ≤ 75.

[0018] As an embodiment of the present application, the negative electrode material includes a carbon material, and the carbon material is at least one of soft carbon, hard carbon, and graphite.

[0019] As an embodiment of the present application, the mass percentage content of sulfur element in the negative electrode material is 0.6 - 3.2%.

[0020] As an embodiment of the present application, the mass percentage content of carbon element in the negative electrode material is 96.2 - 98.4%.

[0021] As an embodiment of the present application, the tap density of the negative electrode material is 0.3 - 0.5 g / cm 3 ; and / or, the average particle size of the negative electrode material is 2 - 10 μm.

[0022] As an embodiment of the present application, the specific capacity of the negative electrode material is 350 - 430 mAh / g.

[0023] The second aspect of the present application provides a negative electrode plate including the above-mentioned negative electrode material.

[0024] As an embodiment of the present application, the sheet resistance of the negative electrode plate is 1.3 - 1.8 mΩ.

[0025] The third aspect of the present application provides a secondary battery including the above-mentioned negative electrode plate.

[0026] The fourth aspect of the present application provides an electrical device including the above-mentioned secondary battery, and the secondary battery serves as the power supply of the electrical device.

[0027] The beneficial effects of this application are as follows: In this application, by controlling the performance and specific surface area of the negative electrode material, the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum, the porosity, and the ratio of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak to satisfy the following relationship: 0.74 ≤ Y ≤ 1.30, where the introduction of sulfur elements can promote the desolvation ability of sodium ion salts in the electrolyte and the rapid adsorption and mass transfer ability of sodium ions, enhance the adsorption energy of sodium ions on the surface of hard carbon, promote the transfer of sodium ions, control the porosity and specific surface area of the negative electrode material, and can effectively improve the ionic conductivity of the negative electrode material, shorten the diffusion path of sodium ions, provide more active sites, promote the insertion and extraction of sodium ions, increase the diffusion rate of sodium ions. The ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum reflects the degree of defect of the negative electrode material, can effectively improve the storage capacity of sodium ions, improve the conductivity and stability of the negative electrode material, and the C-S peak and the S-S peak further improve the conductivity and stability of the material, improve the volume expansion and contraction of the negative electrode material, improve the deintercalation ability of sodium ions, and significantly improve the specific capacity and rate performance of the secondary battery. Detailed Embodiments

[0028] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Apparently, the described embodiments are some, but not all, of the embodiments of this application. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in this application without creative efforts shall fall within the scope of protection of this application.

[0029] In this application, among the technically characterized described in an open-ended manner, it includes a closed technical solution composed of the listed features, and also includes an open technical solution containing the listed features.

[0030] In this application, regarding the numerical range, unless otherwise specified, the above numerical range is considered continuous, and includes the minimum value and the maximum value of this range, as well as each value between such minimum value and maximum value. Further, when the range refers to an integer, it includes each integer between the minimum value and the maximum value of this range. In addition, when providing multiple ranges to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.

[0031] The embodiments of this application provide a negative electrode material, and the negative electrode material contains C-S bonds and S-S bonds;

[0032] The negative electrode material satisfies: 0.74 ≤ Y ≤ 1.30;

[0033] where, Am 2 / g is the specific surface area of the negative electrode material;

[0034] Q% is the porosity of the negative electrode material;

[0035] γ is the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum of the negative electrode material;

[0036] B% is the proportion of the sum of the areas of the C-S peak and the S-S peak in the XPS spectrum of the negative electrode material to the area of the S2p peak.

[0037] The inventors of the present application have found through research that the performance of the negative electrode material has an obvious correlation with the specific surface area, the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum, the porosity, and the proportion of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak. In the present application, by controlling the performance of the negative electrode material, the specific surface area, the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum, the porosity, and the proportion of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak satisfy the following relationship: 0.74 ≤ Y ≤ 1.30. Among them, the introduction of sulfur elements can promote the desolvation ability of sodium ion salts in the electrolyte and the rapid adsorption and mass transfer ability of sodium ions, enhance the adsorption energy of sodium ions on the surface of the negative electrode material, promote the transfer of sodium ions, control the porosity and specific surface area of the negative electrode material, effectively improve the ionic conductivity of the negative electrode material, shorten the diffusion path of sodium ions, provide more active sites, promote the insertion and extraction of sodium ions, increase the diffusion rate of sodium ions. The ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum reflects the defect degree of the negative electrode material, can effectively improve the sodium ion storage capacity, improve the conductivity and stability of the negative electrode material. The C-S peak and the S-S peak further improve the conductivity and stability of the material, improve the volume expansion and contraction of the negative electrode material, improve the deintercalation ability of sodium ions, and significantly improve the specific capacity and rate performance of the secondary battery.

[0038] In one of the embodiments, 300 ≤ A ≤ 1000. For example, it can be 300, 350, 400, 500, 600, 700, 800, 900, 1000 or the range composed of any two of these values. By controlling A within this range, more sodium ion migration channels can be provided, the sodium ion migration path can be shortened, the contact area with the electrolyte can be increased, the formation of the SEI film can be promoted, the compaction density can be improved, the material can be prevented from being broken during the rolling process, the stability of the negative electrode material can be improved, and the specific capacity and rate performance of the secondary battery can be effectively improved.

[0039] In one of the embodiments, 470 ≤ A ≤ 10000.

[0040] In one of the embodiments, 800 ≤ A ≤ 1000.

[0041] It should be noted that in this application, a specific surface area and pore size distribution analyzer is used to test the specific surface area of the negative electrode material, and the test standard is the gas adsorption BET method of GB / T 19587-2017.

[0042] In one of the embodiments, 38 ≤ Q ≤ 68. For example, it can be 38, 40, 42, 46, 48, 54, 56, 60, 62, 66, 68 or the range composed of any two of these values. By controlling the porosity of the negative electrode material within this range, more space can be provided for the insertion and extraction of sodium ions, the expansion and contraction of the negative electrode material can be slowed down, the diffusion rate of sodium ions can be increased, and the specific capacity and rate performance of the secondary battery can be effectively improved.

[0043] Among them, the porosity of the negative electrode material is measured by the mercury intrusion method.

[0044] In one of the embodiments, 58 ≤ Q ≤ 68.

[0045] In one of the embodiments, 1.05 ≤ γ ≤ 1.4. For example, it can be 1.05, 1.08, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4 or the range composed of any two of these values. Among them, the D peak of the Raman spectrum of the negative electrode material is related to the defects, edge structure and disorder degree of the material. Generally, the more defects in the material, the greater the intensity of the D peak. The G peak reflects the vibration of long-range ordered carbon-carbon bonds in the carbon material, and the intensity of the G peak is related to the crystal structure degree and conductivity of the material. The D / G ratio (the intensity ratio of the D peak to the G peak) in the Raman spectrum is usually used to describe the disorder degree or defect density of the material. By controlling it within this range, the storage capacity for sodium ions can be improved, active sites can be provided for the insertion of sodium ions, the initial capacity of the secondary battery can be enhanced, the conductivity and stability of the negative electrode material can be improved, the insertion and extraction of sodium ions can be further promoted, and the specific capacity and rate performance of the negative electrode material can be improved.

[0046] Among them, the ratio of the intensity of the D peak to the intensity of the G peak of the Raman spectrum of the negative electrode material is obtained by the following test method: Take an appropriate amount of the negative electrode material and place it on a glass slide. After pressing and forming with a glass slide, it is tested with a laser. The wavelength of the laser is 532 nm, and the test range is 500 cm -1 ~4000 cm -1 . Among them, the intensity of the D peak represents the intensity of the peak that appears near 1350 cm in the Raman spectrum of the negative electrode material -1 , and the intensity of the G peak represents the intensity of the peak that appears near 1380 cm in the Raman spectrum of the negative electrode material -1 .

[0047] In one embodiment, 48 ≤ B ≤ 75. For example, it can be 48, 52, 55, 56, 58, 60, 62, 65, 68, 70, 72, 75, or a range composed of any two of these values.

[0048] In one embodiment, 65 ≤ B ≤ 75.

[0049] X-ray photoelectron spectroscopy (XPS) is a commonly used surface analysis technique for studying the chemical composition and chemical state of material surfaces. In anode materials, XPS spectra are particularly crucial for the analysis of sulfides and silicon-carbon composites. The S2p peak is the characteristic peak of sulfur element, and the C-S and S-S peaks reflect the chemical bonding between sulfur and carbon atoms. The C-S peak represents sulfur-containing organic functional groups (such as carbon-sulfur bonds), and the S-S peak represents the presence of sulfur-sulfur bonds. The ratio of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak (usually referred to as the C-S / S2p ratio) can reflect the structural information of surface sulfides, the degree of binding between sulfur and carbon on the anode material surface, and the chemical environment of sulfides.

[0050] By controlling B within the above range, the conductivity of the anode material can be improved, a more ordered carbon-sulfur network can be constructed, the electron transport ability of the material can be enhanced, the expansion and contraction of the anode material can be effectively alleviated, the material cracking caused by volume change during charge and discharge of the anode material can be reduced, which helps the formation and stability of the SEI film, reduces the decomposition of the electrolyte, and effectively improves the specific capacity and rate performance of the secondary battery.

[0051] Among them, the test method for the XPS spectrum of the anode material is as follows: In a glove box with a water and oxygen content lower than 0.1 ppm, take a small amount of powder and paste it onto the surface tape of a special sample stage, and then seal and transfer it to the XPS test equipment for testing. The energy range of X-rays is 0 - 1200 eV. In the obtained XPS spectrum, let S1 represent the area of the peak corresponding to the sulfur-carbon bond, S2 represent the area of the S-S peak, and S represent the area of the S2p peak. After calculation, the ratio of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak can be obtained.

[0052] In one embodiment, the carbon material is at least one of soft carbon, hard carbon, and graphite.

[0053] In one embodiment, the mass percentage content of sulfur element in the anode material is 0.6 - 3.2%. For example, it can be 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.2%, or a range composed of any two of these values. By controlling the sulfur element content within this range, the desolvation ability of sodium ion salts in the electrolyte and the rapid adsorption and mass transfer ability of sodium ions can be promoted, and the adsorption energy of sodium ions on the anode material surface can be improved.

[0054] In one embodiment, the mass percentage of carbon element in the negative electrode material is 96.2-98.4%, for example, it can be 96.2%, 96.5%, 97%, 97.5%, 98%, 98.4% or the range composed of any two of these values. By controlling the content of carbon element within this range, the conductivity and stability of the negative electrode material can be improved.

[0055] Among them, the test method for the mass percentage of sulfur element and carbon element in the negative electrode material is as follows: Take 0.5 g of the negative electrode material, add 10 mL of nitric acid, then carry out microwave digestion, and then cool to 70 °C; then, use the calibration curve method to make up the volume to 50 mL with pure water. Inject the sample solution into the injection chamber of the ICP instrument, ionize the substances in the sample by using a high-frequency electric field to generate a plasma, and at the same time ionize and excite the plasma. Use the ICP instrument to perform spectral analysis on the elements in the plasma, and calculate the content of carbon element and sulfur element in the sample according to the emission spectral line intensities of each carbon element and sulfur element.

[0056] In one embodiment, the tapped density of the negative electrode material is 0.3-0.5 g / cm 3 , for example, it can be 0.3 g / cm 3 , 0.32 g / cm 3 , 0.35 g / cm 3 , 0.36 g / cm 3 , 0.38 g / cm 3 , 0.4 g / cm 3 , 0.42 g / cm 3 , 0.45 g / cm 3 , 0.46 g / cm 3 , 0.48 g / cm 3 , 0.5 g / cm 3 or the range composed of any two of these values. By controlling the tapped density of the negative electrode material within this range, the stability of the negative electrode material can be improved, avoiding its breakage during the rolling process, and improving the transmission rate of electrons and ions.

[0057] In one embodiment, the average particle size of the negative electrode material is 2-10 μm, for example, it can be 2 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or the range composed of any two of these values. By controlling the average particle size of the negative electrode material within this range, the ion transmission rate of the material can be improved.

[0058] Among them, the test of the tapped density of the negative electrode material can refer to GB / T5162-2021 Determination of Tapped Density of Metal Powders. The determination method of the average particle size is to measure by using a scanning electron microscope.

[0059] In one embodiment, the specific capacity of the negative electrode material is 350 to 430 mAh / g. For example, it can be 350 mAh / g, 360 mAh / g, 380 mAh / g, 400 mAh / g, 420 mAh / g, 430 mAh / g, or a range composed of any two of these values. This can improve the energy density of the secondary battery.

[0060] Among them, the test method for the specific capacity of the negative electrode material is as follows:

[0061] (1) After grinding and mixing the negative electrode material, acetylene black, carbon nanotubes, and polyvinylidene fluoride evenly according to a mass ratio of 7:1:1:1, add NMP solvent to prepare an electrode slurry. After coating it on a copper foil and vacuum drying at 80 °C for 24 h, punch it into small round pieces with a diameter of 12 mm.

[0062] (2) In a glove box with a water and oxygen content lower than 0.1 ppm, assemble a button cell with a glass fiber separator, 1 mol / L NaPF6 electrolyte (the solvent system is 40:30:30 EC / DEC / FEC), and a sodium metal sheet as the counter electrode.

[0063] (3) Conduct tests on a Neware battery tester. The test voltage range is 0 to 3 V. The capacity measured at a current density of 0.1 A / g is the specific capacity of the negative electrode material.

[0064] In one embodiment, the preparation method of the negative electrode material includes the following steps:

[0065] Mix the carbon source and zinc oxide evenly, carbonize to obtain a first precursor, mix the first precursor with a rubidium compound evenly, and perform high-temperature etching to obtain a second precursor; pass carbon disulfide gas through the second precursor at 200 to 400 °C for sulfidation to obtain the negative electrode material.

[0066] In this application, by using zinc oxide as a template to create pores, the porosity and specific surface area are provided; a rubidium compound is used for etching to increase its defect degree; surface sulfidation is used to improve the ionic conductivity of the surface and interface of the second precursor negative electrode material, and finally a negative electrode with high specific capacity and high rate performance is obtained.

[0067] Among them, zinc oxide is used as a hard template to increase the surface area of the negative electrode material, shorten the ion diffusion path, and promote the diffusion kinetics of sodium ions inside the hard carbon; removing zinc oxide after pickling (pickling temperature 25 °C to 90 °C, pickling time 0.5 to 6 h) can enrich the pores of the carbon material.

[0068] The surface of carbon materials is etched using rubidium compounds (such as rubidium hydroxide) to enhance surface defects and increase sodium storage active sites for sodium ions; rubidium hydroxide (RbOH·xH2O) itself has strong oxidizing properties. Under high-temperature conditions, the process in which the original carbon material reacts with oxygen, gas, or gas molecules to form gaseous products (RbOH + C → Rb2CO3 + H2↑). This causes mass loss and structural changes in the original carbon material, thereby forming a pore structure and active sites. During the subsequent treatment process, the rubidium compound is released through dissociation or desorption.

[0069] By performing sulfidation treatment, sulfur elements are introduced in the form of C-S bonds / S-S bonds in the surface layer region of the material, forming a sulfur-rich interface with a mixture of C-S / S-S bonds on the surface of the hard carbon.

[0070] By controlling the time and temperature of the sulfidation, the ratio of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak in the XPS spectrum of the anode material can be adjusted.

[0071] In one of the embodiments, the carbon source includes at least one of sucrose, glucose, citric acid, polyethylene glycol, and soluble starch.

[0072] In one of the embodiments, the mass ratio of the carbon source to zinc oxide is (2 to 20):1, for example, it can be 2:1, 4:1, 5:1, 6:1, 8:1, 10:1, 12:1, 15:1, 20:1, or a range composed of any two of these values.

[0073] In one of the embodiments, the average particle size of the zinc oxide is 30 to 100 nm, for example, it can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or a range composed of any two of these values.

[0074] In one of the embodiments, the temperature of the carbonization is 800 to 1000 °C, for example, it can be 800 °C, 850 °C, 900 °C, 950 °C, 1000 °C, or a range composed of any two of these values.

[0075] In one of the embodiments, the mass ratio of the first precursor to the rubidium compound is 1:(2 to 5), for example, it can be 1:2, 1:3, 1:4, 1:5, or a range composed of any two of these values.

[0076] In one of the embodiments, the temperature of the high-temperature etching is 700 to 900 °C, for example, it can be 700 °C, 750 °C, 800 °C, 850 °C, 900 °C, or a range composed of any two of these values. By controlling the parameters of the high-temperature etching, the value of the D peak / G peak can be adjusted.

[0077] In one embodiment, the rubidium compound includes rubidium hydroxide.

[0078] In one embodiment, the sulfidation time is 1 to 6 h, for example, it may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, or a range composed of any two of these values.

[0079] More specifically, the method for preparing the negative electrode material includes the following steps:

[0080] Mix a carbon source and zinc oxide evenly, carbonize, remove zinc oxide by pickling, dry to obtain a first precursor, mix the first precursor and a rubidium compound evenly, etch at high temperature, remove the rubidium compound by pickling, dry to obtain a second precursor; pass carbon disulfide gas through the second precursor at 200 - 400 °C for sulfidation, and cool to obtain the negative electrode material.

[0081] One embodiment of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer sequentially provided on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode material, and the negative electrode material includes the above-mentioned negative electrode material.

[0082] As an embodiment of the present application, the sheet resistance of the negative electrode plate is 1.3 - 1.8 mΩ, for example, it may be 1.3 mΩ, 1.4 mΩ, 1.5 mΩ, 1.6 mΩ, 1.7 mΩ, 1.8 mΩ, or a range composed of any two of these values. Controlling the sheet resistance of the negative electrode plate within the above range can reduce the polarization phenomenon of the electrode plate and improve the fast charging performance of the battery.

[0083] The test method for the sheet resistance of the negative electrode plate described in the present application is as follows: Take a sample with an area of 4 cm * 25 cm longitudinally along the negative electrode plate, and test it with a two-probe sheet resistance tester.

[0084] In the present application, there is no particular limitation on the negative electrode current collector, as long as it can achieve the purpose of the present application. For example, it may be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a composite current collector, etc.

[0085] In one embodiment, the negative electrode plate further includes a conductive agent and a binder.

[0086] One embodiment of the present application provides a secondary battery, which includes the above-mentioned negative electrode plate.

[0087] In one embodiment, the secondary battery further includes a positive electrode plate.

[0088] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector.

[0089] In the present application, the type of the positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc., and carbon materials such as carbon cloth and carbon paper. In one embodiment, the positive electrode current collector is a metal material. In one embodiment, the positive electrode current collector is aluminum.

[0090] Among them, the form of the positive electrode current collector is not particularly limited. When the positive electrode current collector is a metal material, the form of the positive electrode current collector can be a metal foil, a metal cylinder, a metal strip coil, a metal plate, a metal foil, a metal plate mesh, a stamped metal, a foamed metal, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector can include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0091] In one embodiment, the positive electrode material layer includes a positive electrode material, and the positive electrode material can be selected from sodium iron composite oxides, sodium cobalt composite oxides, sodium manganese composite oxides, sodium nickel composite oxides, sodium nickel titanium composite oxides, sodium nickel manganese composite oxides, sodium iron manganese composite oxides, sodium nickel cobalt manganese composite oxides, sodium iron phosphate compounds, sodium manganese phosphate compounds, sodium cobalt phosphate compounds, etc. However, the present application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials can also be used. These positive electrode active materials can be used alone or in combination of two or more.

[0092] In one embodiment, the positive electrode material layer further includes a conductive agent and a binder.

[0093] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0094] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0095] In one embodiment, the type of the binder mentioned in the present application is not limited, and any known positive electrode binder can be used.

[0096] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, cellulose nitrate, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene difluoride, and polytetrafluoroethylene-ethylene copolymer.

[0097] In one embodiment, the secondary battery may include an outer package that can be used to encapsulate the above electrode assembly and electrolyte.

[0098] In one embodiment, the outer package of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The outer package of the secondary battery may also be a soft package, such as a pouch soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0099] In one embodiment, the type of the electrolyte is not particularly limited either. Among them, the electrolyte includes an electrolyte salt and an organic solvent, and the specific types of the electrolyte salt and the organic solvent are not particularly limited and can be selected according to actual needs. The electrolyte may further include an additive, and the type of the additive is not particularly limited. It may be a film-forming additive for the positive electrode and / or the negative electrode, or an additive that can improve certain battery performances, such as an additive that improves the high or low temperature performance of the battery.

[0100] In one embodiment, the electrolyte salt includes at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, and sodium hexafluoroarsenate.

[0101] In one embodiment, the organic solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0102] The present application does not particularly limit the shape of the secondary battery, and it may be cylindrical, square, or any other shape.

[0103] One embodiment of the present application provides an electrical device, including the secondary battery described above, and the secondary battery serves as the power supply of the electrical device.

[0104] Exemplarily, the above electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc., but is not limited thereto.

[0105] The following further elaborates the present application with specific embodiments:

[0106] Example 1

[0107] A method for preparing a secondary battery includes the following steps:

[0108] (1) Preparation of the negative electrode plate

[0109] Preparation of the negative electrode material: Take 120 g of sucrose and 20 g of ultra-fine zinc oxide (average particle size 200 nm), stir and dissolve in 500 mL of deionized water. After freeze-drying, put it into a tube furnace and carbonize at 900 °C for 4 h. After taking it out, stir and pickling with 300 mL of HCl (3 mol / L) to remove the zinc oxide template, and then freeze-dry to obtain the first precursor; mix the first precursor and rubidium hydroxide evenly according to the mass ratio of 1:3, put it into a nickel crucible, and carry out an etching reaction at 800 °C for 4 h, pickling to neutrality, and then freeze-dry to obtain the second precursor; carry out surface sulfidation of the second precursor in a tube furnace. Put the second precursor into a crucible, and pass carbon disulfide at 350 °C for carbon material sulfidation. The sulfidation time is 2 h to obtain a hard carbon negative electrode material.

[0110] Mix the hard carbon negative electrode material, acetylene black, carbon nanotubes, and polyvinylidene fluoride according to the mass ratio of 7:1:1:1, grind and mix evenly, prepare electrode paste, coat it on a 6-μm-thick copper foil, and then vacuum-dry at 80 °C for 24 h, and then punch it into a negative electrode plate with a thickness of 12 mm.

[0111] (2) Assembly of the secondary battery: In a glove box with a water and oxygen content lower than 0.1 ppm, assemble a button cell with a 20-μm-thick glass fiber separator, a 1 mol / L NaPF6 electrolyte (the solvent system is 40:30:30 EC / DEC / FEC), and a sodium metal sheet as the counter electrode.

[0112] The parameters of the negative electrode material in Example 1 are shown in Table 1.

[0113] Example 2

[0114] The difference between Example 2 and Example 1 lies in the different preparation methods of the negative electrode material.

[0115] Preparation of the negative electrode material: Take 120 g of sucrose and 20 g of ultrafine zinc oxide, stir and dissolve them in 500 mL of deionized water. After freeze-drying, put them into a tube furnace and carbonize at 950 °C for 5 h. After taking out, stir and pickle with 300 mL of HCl (3 mol / L) to remove the zinc oxide template, and then freeze-dry to obtain the first precursor; Mix the first precursor and rubidium hydroxide evenly according to a mass ratio of 1:3.5, put them into a nickel crucible, and carry out an etching reaction at 700 °C for 2 h. After pickling to neutrality and freeze-drying, obtain the second precursor; Carry out surface sulfidation of the second precursor in a tube furnace. Put the second precursor into a crucible, introduce carbon disulfide at 300 °C for carbon material sulfidation, and the sulfidation time is 3 h to obtain the hard carbon negative electrode material.

[0116] Example 3

[0117] The difference between Example 3 and Example 1 is that the preparation method of the negative electrode material is different.

[0118] Preparation of the negative electrode material: Take 120 g of sucrose and 20 g of ultrafine zinc oxide, stir and dissolve them in 500 mL of deionized water. After freeze-drying, put them into a tube furnace and carbonize at 800 °C for 3 h. After taking out, stir and pickle with 300 mL of HCl (3 mol / L) to remove the zinc oxide template, and then freeze-dry to obtain the first precursor; Mix the first precursor and rubidium hydroxide evenly according to a mass ratio of 1:4, put them into a nickel crucible, and carry out an etching reaction at 850 °C for 5 h. After pickling to neutrality and freeze-drying, obtain the second precursor; Carry out surface sulfidation of the second precursor in a tube furnace. Put the second precursor into a crucible, introduce carbon disulfide at 400 °C for carbon material sulfidation, and the sulfidation time is 3 h to obtain the hard carbon negative electrode material.

[0119] Examples 4-5, Comparative Examples 1-3

[0120] The difference between Example 4 and Example 2 is that the carbonization temperature is 450 °C and the carbonization time is 3 h.

[0121] The difference between Example 5 and Example 2 is that the carbonization temperature is 550 °C and the carbonization time is 4 h.

[0122] The difference between Comparative Example 1 and Example 2 is that the carbonization temperature is 400 °C and the carbonization time is 3 h.

[0123] The difference between Comparative Example 2 and Example 2 is that the carbonization temperature is 300 °C and the carbonization time is 4 h.

[0124] The difference between Comparative Example 3 and Example 2 is that the carbonization temperature is 500 °C and the carbonization time is 5 h.

[0125] Examples 6 - 9, Comparative Example 4

[0126] Example 6 is different from Example 2 in that the etching temperature is 500 °C and the etching time is 3 h.

[0127] Example 7 is different from Example 2 in that the etching temperature is 550 °C and the etching time is 4 h.

[0128] Example 8 is different from Example 2 in that the etching temperature is 900 °C and the etching time is 2 h.

[0129] Example 9 is different from Example 2 in that the etching temperature is 650 °C and the etching time is 5 h.

[0130] Comparative Example 4 is different from Example 2 in that the etching temperature is 450 °C and the etching time is 3 h.

[0131] Examples 10 - 11

[0132] Example 10 is different from Example 2 in that the mass ratio of the precursor to rubidium hydroxide is 1:2.

[0133] Example 11 is different from Example 2 in that the mass ratio of the precursor to rubidium hydroxide is 1:2.5.

[0134] Examples 12 - 13

[0135] Example 12 is different from Example 2 in that the sulfidation temperature is 250 °C and the sulfidation time is 6 h.

[0136] Example 13 is different from Example 2 in that the sulfidation temperature is 350 °C and the sulfidation time is 5 h.

[0137] Table 1 Parameter Table

[0138]

[0139]

[0140] Performance Test

[0141] The test was carried out on a Neware battery tester, and the test voltage range was 0 - 3 V. The specific capacity performance test was carried out at a current density of 0.1 A / g.

[0142] Negative electrode sheet film resistance: A 4 cm * 25 cm area sample was taken longitudinally along the negative electrode sheet, and the film resistance was measured using a two - probe film resistance tester.

[0143] Initial Coulombic efficiency: In the assembled button battery, the charging capacity / discharging capacity is the initial Coulombic efficiency.

[0144] Table 2 Performance Test Table

[0145]

[0146] As can be seen from Table 1, in this application, by controlling the performance and specific surface area of the negative electrode material, the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum, the porosity, and the ratio of the sum of the areas of the C-S peak and the S-S peak to the area of the S2p peak satisfy the following relationship: 0.74 ≤ Y ≤ 1.30, significantly improving the specific capacity and rate performance of the secondary battery.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application rather than to limit the protection scope of this application. Although this application has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of this application can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of this application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material contains CS bonds and SS bonds; The negative electrode material satisfies: 0.74≤Y≤1.30; Among them, Am 2 / g is the specific surface area of ​​the negative electrode material; Q% is the porosity of the negative electrode material; γ is the ratio of the D peak intensity to the G peak intensity of the Raman spectrum of the negative electrode material; B% is the ratio of the sum of the CS peak area and the SS peak area to the S2p peak area in the XPS spectrum of the negative electrode material.

2. The negative electrode material according to claim 1, characterized in that Satisfy at least one of the following (I) to (IV): (Ⅰ)300≤A≤1000; (Ⅱ)38≤Q≤68; (III) 1.05≤γ≤1.4; (Ⅳ)48≤B≤75。 3. The negative electrode material according to claim 1, characterized in that The negative electrode material includes a carbon material, and the carbon material is at least one of soft carbon, hard carbon, and graphite.

4. The negative electrode material according to claim 1, characterized in that The mass percentage of sulfur in the negative electrode material is 0.6-3.2%; and or the mass percentage of carbon in the negative electrode material is 96.2-98.4%.

5. The negative electrode material according to claim 1, characterized in that The tap density of the negative electrode material is 0.3 to 0.5 g / cm 3 .

6. The negative electrode material according to claim 1, characterized in that The specific capacity of the negative electrode material is 350 to 430 mAh / g.

7. The negative electrode material according to claim 1, characterized in that The average particle size of the negative electrode material is 2 to 10 μm.

8. A secondary battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material according to claims 1 to 7.

9. The secondary battery according to claim 8, characterized in that: The film resistance of the negative electrode plate is 1.3-1.8 mΩ.

10. An electrical device, characterized in that: It comprises the secondary battery described in any one of claims 8 to 9, wherein the secondary battery is used as a power supply for the electrical device.